P36 Evaluation to assess patients' perceptions of receiving the recent infection testing algorithm [RITA] result. (23rd May 2012) - Gilbart, V; Anderson, E; Garrett, N; Perera, S; Rayment, M; Williams, H; Tosswill, J H; Delpech, V
Abstract : Background: In the UK the primary objective of RITA has been to measure HIV incidence. The UK is the first country to routinely return results to patients and with over 7000 tests returned to clinicians so far, RITA is now seen as part of baseline HIV clinical care in participating centres. Objectives: To evaluate patients' experience of receiving a RITA result, including effects on identifying likely timing of infection, partner notification and relationships. Methods: Five HIV centres in England asked their patients to complete a questionnaire on their experience of receiving a "recently infected" RITA result soon after their HIV diagnosis. Results: Forty patients with newly diagnosed HIV and a "recent" RITA result completed the questionnaire (93% MSM). The majority (30/40, 75%) said that receiving the recent RITA result was helpful; 10 were unsure how helpful it was, and no participants found it unhelpful. 24 patients (60%) reported RITA helped identify partners who may be at risk of HIV and 24 (62%) felt it helped them to better understand how they may have been infected. Most (35, 88%) either felt neutral or "not more upset" when they learnt that they were likely recently infected. Of those in a relationship 33/37 (89%) reported RITA testing had not caused any relationship problems. Conclusion: The majority of patients receiving recent RITA results found this information helpful and no-one found it unhelpful. The result was felt to be useful in increasing an understanding of the likely timing of infection and for identifying "at risk" partners.